2023
DOI: 10.56536/ijmres.v13i1.376
|View full text |Cite
|
Sign up to set email alerts
|

Relationship of Corporate Social Responsibility and Impulse Buying: Role of Corporate Reputation and Consumer Company Identification

Abstract: This study aims to explore the influence of CSR on consumers' impulse buying behavior and examine the most dominant practices for CSR, which stimulate the consumers for impulse buying with the mediation effect of corporate reputation and consumer company identification. Because corporate social responsibility is an important source of significant transformation in society. The intention of this change is to consumers' reactions in response to CSR implications. Developed a set of hypotheses to check the affilia… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 80 publications
0
5
0
Order By: Relevance
“…Environmental, economic, and social well-being are the most important factors in establishing trust and play a crucial role in impulse purchasing. According to another study, due to the perception of the socially responsible business, social well-being actions have a direct impact on consumers' impulse buying intention [21]. In addition, previous research found that environmental and economic well-being are found to have a positive effect on consumers' impulse buying [85].…”
Section: Discussionmentioning
confidence: 95%
See 4 more Smart Citations
“…Environmental, economic, and social well-being are the most important factors in establishing trust and play a crucial role in impulse purchasing. According to another study, due to the perception of the socially responsible business, social well-being actions have a direct impact on consumers' impulse buying intention [21]. In addition, previous research found that environmental and economic well-being are found to have a positive effect on consumers' impulse buying [85].…”
Section: Discussionmentioning
confidence: 95%
“…Businesses prioritize the interests of their employees, communities, shareholders, and the public [42]. These efforts help society progress in the long run and give businesses an edge in the competitive marketplace [21]. The three cornerstones of CSR include environmental, social, and economic well-being and have been extensively practiced by organizations.…”
Section: Sustainable Csr Practices and Impulsive Buying Intentionmentioning
confidence: 99%
See 3 more Smart Citations